A novel plant‐station and inter‐plant‐station topology analysis method. (27th May 2015) - Ma, Jing; Yan, Xin; Zhang, Yuyu; Lin, Yifeng; Wang, Zengping; Thorp, James S.
Summary: In view of the requirement for instantaneity on power system topology analysis, a novel power system topology analysis method is proposed in this paper. For the plant‐station topology method, the nodes that represent the circuit breakers are numbered according to the graph theory. On this basis, combining the main wiring characteristics and the switch status information, the plant‐station topology is analyzed using the topological base theorem. When the switch status changes, the affected part of topology is modified using the radius search method, so that reforming of the topology is avoided and fast update of topology is guaranteed. When dealing with inter‐plant‐station topology, the incidence matrix notation method is used to judge the connectivity of the graph and mark the tree branches and link branches in the network, thus conducting static topology analysis of the power network. And then, when the network topology changes, the property of the changing branch is determined with the help of the loop matrix. On this basis, the local network topology and the loop matrix are updated by means of the broken circle method and the radius search method. Calculation examples verify the advantage of the proposed methods over traditional methods in calculation speed. With the proposed topology analysis methods, fast tracking of the switch status can be realized. Copyright © 2015 John Wiley & Sons, Ltd.